PENTINGNYA WARMING UP DAN COOLING DOWN UNTUK MENGHINDARI CEDERA DALAM OLAHRAGA - Nimrot Manalu; Muhammad Rizki Putra; Steven Parninggotan Pardede; Fendra Ananta Lubis; Muhammad Arif; Andes Martua Harahap (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study evaluates the importance of warming up and cooling down during exercise to reduce the risk of injury. Using qualitative methods through a literature review of journals and scientific articles, it was found that warming up plays a crucial role in physical and mental preparation, improving performance, and enhancing focus. Warming up can be implemented actively through general, dynamic, and preventative movements. Cooling down—whether active (low-intensity) or passive (such as immersing in cold water)—functions to return the body to a calm state, lower the heart rate, and reduce muscle soreness. Therefore, both activities are essential for preventing injury and maintaining long-term fitness.